ANALISIS KINERJA APARATUR SIPIL NEGARA (ASN) PADA BADAN PENGELOLA KEUANGAN DAERAH (BPKD) KOTA TANGERANG (Studi Bidang Sekretariat BPKD) - Suryani Suryani; Dafyar Eliadi H; Ambuy Sabur (Perspektif : Jurnal Ilmu Administrasi, 2023)
This study aims to analyze Employee Performance at the Tangerang City Regional Financial Management Agency (case study of the Secretariat field). The approach used in this research is a qualitative approach, which is based on the author's observations in the field, the actual situation found during the research is described by collecting data, clarifying and analyzing to obtain a formulation to analyze the problem at hand. Qualitative research methods are then used, which try to provide a description of the situation in the field, so that the method aims to collect data to draw conclusions from the research. The results of this study indicate that: 1. The quality of performance services with motivation and encouragement when carrying out tasks at the Tangerang City Regional Financial Management Agency, seems to pay less attention to employee performance and rarely provides encouragement to employees and motivation is always given, in different ways and forms. 2. Accountability to the internal and external environment at the Regional Financial Management Agency of Tangerang City, the influence of the environment on employee performance is quite high but not yet optimal and the performance report (LKIP) of the Regional Financial Management Agency (BPKD) of Tangerang City in 2021 was prepared in order to fulfill the provisions of Presidential Regulation Number 29 of 2014 concerning the Performance Accountability System of Government Agencies, which is a form of accountability for the implementation of the tasks assigned to BPKD Tangerang City within 2021. Keywords: Performance Analysis, Civil Apparatus, Regional Financial Management Agency